FLYPAPER EFFECT PADA PENGELUARAN PEMERINTAH DAERAH DI JAWA - Pramuka, Bambang Agus (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2010)
This study analysis whether there is any flypaper effect in local governmentsâ expenditures, and whether there are significant influences of grants from central government and original revenue of local governments on their expenditures, especially the operating and capital expenditures. The object of the study are all local autonomous governments in Java; and the focus of the study was the financial statement of the 2005-2008 fiscal year. Through an examination on financial statement of all kabupatens and kotas in Java, and applying multiple regression analysis, it is revealed that the flypaper effect was not found, which implied that the local government did not rely more on grant from the central government as the sources of their budget. The DAU (grant) and PAD (original revenues), however, were found to be significantly influencing the operating, capital, and total of local government expenditures, for the related year and the following year.